EDUCATIONAL AND PEDAGOGICAL MECHANISMS FOR THE DEVELOPMENT OF AESTHETIC CULTURE ON THE BASIS OF LOCAL HISTORY MUSEUMS - Siddikov Dilshod (Innovate Conferences, 2025)
This article analyzes the didactic and educational capabilities of local history museums in the formation of the aesthetic culture of future educators.nnotation. This article analyzes the didactic and educational capabilities of local history museums in the formation of the aesthetic culture of future educators. In the process of research, the influence of the museum environment on the aesthetic conscionnotation. This article analyzes the didactic and educational capabilities of local history museums in the formation of the aesthetic culture of future educators. In the process of research, the influence of the museum environment on the aesthetic consciousness of the individual, the role of historical and cultural exhibits in the development of aesthetic perception are highlighted from a pedagogical point of view. Also, the importance of innovative methods used in museum pedagogy – interactive training, digital technologies, visual-educational resources in the development of aesthetic thinking and artistic taste is revealed. The article scientifically substantiates local history museums as an important aesthetic resource that serves the spiritual and spiritual development of students in the educational process.
Keywords: Museum of local lore, aesthetic consciousness, aesthetic education, Museum pedagogy, cultural heritage, aesthetic perception, artistic thinking, aesthetic taste, aesthetic need, interactive education, visual tools.